A study on the consumer knowledge of green technology towards environment and green products / Malia Mohamed and Noorhuda Harun - Mohamed, Malia; Harun, Noorhuda (2011)
As the environment continues to worsen, it becomes a persistent public concern in the developed countries and recently awakens developing countries to the green movement. This paper is essentially exploratory in nature and has four objectives. The first objective is to examine the consumers’ knowledge of GT towards the environment and green products. The second objective is to investigate the relationship between dependent variable (Knowledge of GT) and the independent variables, i.e. Health and Safety, Media exposure, Personal norms and Government role. The third objective is to identify which is the most important variable that influences the knowledge level. By using nonprobability sampling which is convenient sampling. The questionnaires for this study were administered to 384 samples among youths in Dungun. The four independent variables consist of Health and safety, Media exposure, personal norm and government’s role indicates each factor significant each other. Results from the multiple linear regression analysis revealed that factors of Health and safety, Media exposure, their Personal norm and Government role towards the environment and green products contributed significantly to their knowledge of GT. Further investigation revealed that Health and safety was the most important contributor, second contributor is Media exposure, followed by Government role and lastly Personal norms to towards environment and green products. The last objective is to propose of several elements in order to create knowledge of GT which can be implementing and brings benefits to consumers. Finally, limitation and future research also included in this study.